Motivators and barriers to using information and communication technology in everyday life following stroke: a qualitative and video observation study. Issue 14 (2nd July 2020) - Lemke, Mailin; Rodríguez Ramírez, Edgar; Robinson, Brian; Signal, Nada
Abstract: Purpose: Information and communication technology devices have become a ubiquitous part of everyday life and a primary means of communication. The aim of this study was to describe the experience of information and communication technology and to explore the barriers and motivators to its use following stroke. Materials and methods: This observational study used semi-structured individual interviews and video observation of information and communication technology device use with six people, four men, and two women age 60–82 years with upper limb disability following stroke. They were analyzed using thematic analysis. Results: Three themes were identified that relate to barriers: (i) Sensory and motor impairments; (ii) Limited vision and impaired speech; and (iii) Device-specific limitations. Six themes were identified as motivators: (i) Connect with others; (ii) Provide safety; (iii) Facilitate reintegration; (iv) Reinforce technology adoption; (v) Leisure activities; and (vi) Contribute to the rehabilitation process. Conclusion: All participants used some form of information and communication technology daily to promote safety, enable daily activities, and social interaction, and to a lesser extent engage in leisure and rehabilitation activities. Barriers to information and communication technology use were primarily related to stroke related impairments and device-specific requirements, which limited use, particularly of smartphones. These barriers should be addressed to facilitate the use of information and communication technology devices. Implications for rehabilitation: This research suggests that; People with stroke are highly motivated to use information and communication technology devices in daily activities Stroke-specific and age-related impairments limit the use and functionality of information and communication technology devices for people with stroke Information and communication technology devices do not appear to be promoted or used in the rehabilitation or as assistive technologies